Translingual neural stimulation induced changes in intra- and inter-network functional connectivity in mild-moderate traumatic brain injury patients - Chu, Daniel Y.; Hou, Jiancheng; Hosseini, Thomas; Nair, Veena A.; Adluru, Nagesh; Danilov, Yuri; Kaczmarek, Kurt A.; Meyerand, Mary E.; Tyler, Mitchell; Prabhakaran, Vivek (Frontiers in Human Neuroscience, 2025)
IntroductionMild-to-moderate traumatic brain injury (mmTBI) that lead to deficits in balance and gait are difficult to resolve through standard therapy protocols, and these deficits can severely impact a patient's quality of life. Recently, translingual neural stimulation (TLNS) has emerged as a potential therapy for mmTBI-related balance and gait deficits by inducing neuroplastic changes in the brain gray matter structure. However, it is still unclear how interactions within and between functional networks in brain are affected by TLNS. The current study aimed to extend our previous resting-state functional connectivity (RSFC) study investigating the effects of TLNS intervention on outcome measures related to gait and balance.MethodsAn experimental PoNS device was utilized to deliver the TLNS. The 2-week TLNS intervention program, specifically stimulation during focused physical therapy focused on recovery of gait and balance, included twice-daily treatment in the laboratory and the same program at home during the intervening weekend. The resting-state fMRI datasets at pre- and post-interventions were collected by 3T MRI scanner with nine mmTBI patients. All participants also received both Sensory Organization Test (SOT) and Dynamic Gait Index (DGI) testing pre- and post-intervention as part of the behavioral assessment.ResultsCompared to baseline, TLNS intervention led to statistically significant improvements in both the SOT [t(8) = 2.742, p = 0.028] and the DGI [t(8) = 2.855, p = 0.024] scores. Moreover, significant increases in intra- and inter-network RSFC were observed, particularly within the visual, default mode, dorsal attention, frontoparietal (FPN), and somatosensory (SMN) networks. Additionally, there were significant correlations between the SOT and inter-network FC [between FPN and SMN, r(9) = –0.784, p = 0.012] and between the DGI and intra-network FC [within SMN, r(9) = 0.728, p = 0.026].DiscussionThese findings suggest that TLNS intervention is an effective in increasing somatosensory processing, vestibular-visual interaction, executive control and flexible shifting, and TLNS may be an effective approach to inducing brain network plasticity and may serve as a potential therapy for mmTBI-related gait and balance deficits.